Living with epilepsy: patient knowledge and psychosocial impact - O. P. Musekwa; L. Makhado (Эпилепсия и пароксизмальные состояния)
Background. People living with epilepsy (PLWE) often face psychological comorbidities and social challenges due to low levels of knowledge and awareness about epilepsy, as well as personal experiences with the condition. This can result in a low quality of life for PLWE.Objective: to investigate the psychosocial impact of epilepsy on patients residing in rural regions of South Africa (Limpopo and Mpumalanga Provinces).Material and methods. A non-experimental quantitative research was conducted, which involved 162 respondents living with epilepsy. Most were males, and the majority were between 18 and 35 years old in both provinces combined. The participants were offered a questionnaire divided into three sections comprising sociodemographic aspects, questions that assessed knowledge, and questions on the psychosocial impact of epilepsy.Results. I t was shown that while PLWE have a solid understanding of epilepsy as a medical condition, they may not fully comprehend its effects on daily life. For example, many respondents felt shameful after having a seizure and difficulties in forming relationships, and a significant proportion stated that they were never married because of epilepsy. The study highlights the significant psychosocial impact of epilepsy on PLWE, including depression, difficulties in forming and maintaining social connections, and a lack of marital experience.Conclusion. To improve PLWE’s quality of life, the psychological help is recommended through healthcare facilities or local support groups.